DETERMINATION OF APPLICATIONS TYPES OF DISEASE IN CHILDREN WITH DRUG AND HOW TRADITIONAL HEALING USING MICROSOFT VISUAL BASIC 6.0 - Diah Fitaloka; Ire Puspa Wardhani. Skom. MMSi Ire Puspa Wardhani. Skom. MMSi (Jurnal Sistem Informasi, 2002)
Writing consists of four chapters, where the first chapter explains the background ofthe problem, purpose of writing, the problem and the problem definition, and researchmethods.In the second chapter, the authors make the basic theories used in solving problems inthe first chapter. In addition there are also explanations regarding the type of programused to help solve the problems authors are computerized.Analysis of problems in the form of the symptoms suffered and the treatmentdescribed in the third chapter, where the explanation of the name of disease and drugmaterial and its use. Here are given hypo, Pseudocode and folwchart and designinputs that give a description of the course of the program.The conclusion of this chapter is contained in chapter four is a medicinal plant that isall around us be utilized as an alternative medicine without great cost and withoutside effects.